THE EFFECT OF JOB SATISFACTION AND TRANSFORMATIONAL LEADERSHIP ON KNOWLEDGE SHARING WITH LEARNING ORIENTATION AS A MEDIATION VARIABLE - Putri, Olsi; Sefnedi, Sefnedi; Yuliviona, Reni (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The objective of this study For analyze and prove empirically is learning orientation mediates the connection between transformational leadership with shared knowledge at SMAN in District IV Jurai Regency South Coast. Which type of study used is a causal study with a quantitative approach? Population And sample study This is all ASN teachers a total of 115 people on year lessons 2022/2023 that work on all public high schools in District IV Jurai Regency South Coast. The instrument study uses a questionnaire. Technique analysis in study This use analysis Smart Partial Least Square (Smart-PLS) statistics were used For test validity, test reliability, test RSquare, and test hypothesis. The results of this study prove that job satisfaction and learning orientation are not influential to share knowledge, meanwhile, leadership transformational is influential and positive to share knowledge. Learning Orientation mediated connection between Work satisfaction And knowledge sharing (not supported). Learning Orientation mediated connection between transformational leadership and knowledge sharing (not supported).